Analysis of the Effect of Work Motivation and Employee Engagement on Turnover Intention Mediated by Employee Performance at PT Bank Mandiri (Persero) Tbk. Case Study on Special Asset Management Group Employees PT Bank Mandiri (Persero), Tbk - Charisna Putra; Muhammad Asdar; Abdul Munir (Pascasarjana STIE Amkop Makassar, 2023)
The purpose of this study is to investigate how employee performance at PT Bank Mandiri (Persero) Tbk mediates the relationship between work motivation and employee engagement and turnover intention. In order to collect data for this study, a questionnaire is used in a quantitative manner. 55 workers of the Special Asset Management Group at the head office and 10 regional areas participated in this survey. Structural Equation Modeling (SEM) via the Partial Least Squares (PLS) software is the instrument used to process data. It was discovered during preliminary testing that all of the variables were deemed viable, legitimate, and reliable based on the measurement model (outer model), structural model (inner model), and the link between the variables. Nearly all variable associations were determined to have a significant effect based on the findings of the hypothesis test, with the exception of the link between the variables of work motivation and turnover intention, which was not significant. This is because the two variables' regression yielded P-values of 0.122, which is higher than the 0.05 cutoff limit. However, the regression association between the Work Motivation and Turnover Intention variables can be changed from originally being insignificant to substantial (full mediation) by the Employee Performance variable, which functions as an intervening variable. Kata Kunci: Work Motivation, Employee Engagement, Turnover Intention, Employee Performance.